Metodologi Ilmu Tarannum Raghīb Muṣṭafā Ghalwasy: Suatu Tinjauan Awal: Methodology of Tarannum Science of Raghīb Muṣṭafā Ghalwasy: An Early Review - Ibrahim, Muhammad Lukman (Jurnal Usuluddin, 2020)
Reciting the Qur’an is amongst the most recommended rituals in Islam. More than that is reciting the Qur’an with tarannum and beautiful voice. This will bring the light of the miracle to the people again. This article aims to introduce the famous qari figure of Egyptian state Raghīb Muṣṭafā Ghalwasy. This article also looks at the methodology used by him in presenting his readings. Besides looking at the methodology of other leading Egyptian qari leaders like Muṣṭafā Ismā’īl and ‘Abd al-Basīṭ’ Abd al-Ṣamad, who has become the most followed qari in Malaysia.